Hydraulic Simulation of Flood Occurrences in a Tropical River System: the Case of Linggi River System - Said, Salim; Mohammed, Thamer Ahmed; Bardaie, Muhamad Zohadie; Nor Basri, Shah (Universiti Putra Malaysia Press, 2002)
Flood forecasting is important because it can help in reducing the consequences of flood damage especially at the downstream end. Advances in numerical methods and computer technologies, have resulted in the development of many mathematical models which can be used for hydraulic simulation of flood. These simulations usually include the prediction of the extent of flood and its depth along a river system. Information obtained from the simulated models are essential because it can help engineers to take precautionary measures in designing their hydraulic structures. Hydraulic models that are used in the simulation can be classified into dynamic hydraulic models and static hydraulic models. The HEC-2 static hydraulic model was used to predict the flow of Linggi river in the vicinity of Seremban town. HEC-2 model is based on the numerical solution of a one-dimensional energy equation of the steady gradually varied flow using an iteration technique. Calibration and verification of the HEC-2 model were conducted using the recorded data for the Linggi river. After calibration, the model was used to predict the water surface profiles for ~, Q10' and Q100 along the watercourse of the Linggi river. The predicted water surface profiles were found to be in agreement with the recorded water surface profiles, whereby the maximum computed value of the absolute error in the predicted water surface profile was found to be 100 mm while the minimum absolute error was found to be 20 mm only. In term of percentage, these errors represent a difference of less than 5% between the readings of the computed simulation to the actual field records. Testing process showed that HEG-2 model is sensitive to value of Manning coefficient of roughness and the intervals of cross sections long studied river system.